PI3K regulates integrin-dependent processes in neutrophils by signalling through its effector ARAP3 - Gambardella, Laure (2012)
ARAP3, a GTPase activating protein for Rho and Arf family GTPases, is one of many PI3K effectors. Here we investigate the regulatory input of PI3K upstream of ARAP3, by analysing neutrophils from an ARAP3 PH domain point mutation knock-in mouse (R302, 303A), in which ARAP3 is uncoupled from activation by PI3K. ARAP3 PH domain point mutant neutrophils are characterised by disturbed responses linked to stimulation by either integrin ligands or immobilised immune complexes. These cells exhibit increased β2 integrin inside-out signalling (binding affinity and avidity), and our work suggests the disturbed responses to immobilised immune complexes are secondary to this. In vitro, neutrophil chemotaxis is affected in the mutant. In vivo, ARAP3 PH domain point mutant bone marrow chimeras exhibit reduced neutrophil recruitment to the peritoneum on induction of sterile peritonitis and also reduced inflammation in a model for rheumatoid arthritis. The present work suggests a dramatic regulatory input of PI3K into the regulation of β2 integrin activity, and processes dependent on this, by signalling through its effector ARAP3.